Removal of ASAM 4th Edition Withdrawal Management Standards: Implementation Risks - Nadia Haddad; Michelle Gaffaney; Smita Das (Journal of Addiction Medicine, 2026)
The release of the ASAM criteria 4 th edition marks a paradigm shift by removing standalone Withdrawal Management levels (3.7-WM/3.2-WM) in favor of an integrated treatment model. Although intended to reduce care fragmentation, inflexible implementation of this transition creates unintended consequences for patient safety and access in states like Colorado, where ASAM criteria are codified in statute. Critical risks include a reimbursement gap for high-acuity monitoring, barriers to entry for patients whose treatment goals mismatch their level of need for withdrawal management, and the potential undoing of harm reduction policies. To mitigate these risks, we propose acuity-based tiered reimbursement, formalized pathways to allow for standalone withdrawal management in partnership with treatment levels of care, and state data tracking to fully realize the impacts of the ASAM criteria updates.